2016
DOI: 10.1097/aud.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Load and Listening Effort: Concepts and Age-Related Considerations

Abstract: Listening effort has been recognized as an important dimension of everyday listening, especially with regard to the comprehension of spoken language. At constant levels of comprehension performance, the level of effort exerted and perceived during listening can differ considerably across listeners and situations. In this article, listening effort is used as an umbrella term for two different types of effort that can arise during listening. One of these types is processing effort, which is used to denote the ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 62 publications
3
59
0
Order By: Relevance
“…A similar explanation can be inferred from a cognitive perspective, where enhanced envelope tracking could reflect the inefficient use of cognitive resources (Presacco et al 2016a) or the increased effort that older adults experience (e.g., Anderson Gosselin and Gagné 2011;Degeest et al 2015;Lemke and Besser 2016). In line with Presacco et al (2016a), we found that enhanced envelope tracking was associated with lower scores on the Stroop test, especially when the matrix sentences were presented.…”
Section: Neural Tracking Of the Speech Envelope And Modulations Of Nosupporting
confidence: 89%
“…A similar explanation can be inferred from a cognitive perspective, where enhanced envelope tracking could reflect the inefficient use of cognitive resources (Presacco et al 2016a) or the increased effort that older adults experience (e.g., Anderson Gosselin and Gagné 2011;Degeest et al 2015;Lemke and Besser 2016). In line with Presacco et al (2016a), we found that enhanced envelope tracking was associated with lower scores on the Stroop test, especially when the matrix sentences were presented.…”
Section: Neural Tracking Of the Speech Envelope And Modulations Of Nosupporting
confidence: 89%
“…This consistent finding suggests that dual-task experimental paradigms may not measure the same attributes of listening effort as the concepts used by listeners when asked to rate the effort that was required to perform a specified speech-understanding task. Accordingly, Lemke and Besser (2016) have suggested that the term listening effort should be used as an umbrella term for processing effort (in terms of resource allocation) during listening on the one hand and for perceived effort (self-reported experience) on the other hand. McGarrigle et al.…”
Section: Resultsmentioning
confidence: 99%
“…Even though objective and subjective results are complementary, it should be noted that they do not necessarily measure the same underlying processes. Given that listening effort is a complex, multifactorial concept, Lemke and Besser (2016) argue that subjective and objective measures can assess different aspects of this concept.…”
Section: Discussionmentioning
confidence: 99%